Transcriptome Sequencing of Gynostemma pentaphyllum to Identify Genes and Enzymes Involved in Triterpenoid Biosynthesis - Qicong Chen; Chengtong Ma; Jieying Qian; Xiuwan Lan; Naixia Chao; Jian Sun; Yaosheng Wu (International Journal of Genomics)
G. pentaphyllum (Gynostemma pentaphyllum), a creeping herbaceous perennial with many important medicinal properties, is widely distributed in Asia. Gypenosides (triterpenoid saponins), the main effective components of G. pentaphyllum, are well studied. FPS (farnesyl pyrophosphate synthase), SS (squalene synthase), and SE (squalene epoxidase) are the main enzymes involved in the synthesis of triterpenoid saponins. Considering the important medicinal functions of G. pentaphyllum, it is necessary to investigate the transcriptomic information of G. pentaphyllum to facilitate future studies of transcriptional regulation. After sequencing G. pentaphyllum, we obtained 50,654,708 unigenes. Next, we used RPKM (reads per kilobases per million reads) to calculate expression of the unigenes and we performed comparison of our data to that contained in five common databases to annotate different aspects of the unigenes. Finally, we noticed that FPS, SS, and SE showed differential expression of enzymes in DESeq. Leaves showed the highest expression of FPS, SS, and SE relative to the other two tissues. Our research provides transcriptomic information of G. pentaphyllum in its natural environment and we found consistency in unigene expression, enzymes expression (FPS, SS, and SE), and the distribution of gypenosides content in G. pentaphyllum. Our results will enable future related studies of G. pentaphyllum.